2004
DOI: 10.1007/s00122-004-1609-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of chloroplast variation in Italian populations of beech (Fagus sylvatica L.)

Abstract: The distribution of chloroplast DNA (cpDNA) variation in Italian beech ( Fagus sylvatica L.) populations was studied using PCR-RFLP and microsatellite markers. In total, 67 populations were analysed, and 14 haplotypes were identified by combining the two marker types. A remarkable subdivision of cpDNA diversity in Italian beech was found, as indicated by a high level of genetic differentiation ( G(st)=0.855). The highest level of total haplotype diversity ( h(t)=0.822) was estimated for southern Italian popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 32 publications
8
57
1
1
Order By: Relevance
“…Peculiar is a genetic proximity and even partial sharing of chloroplast haplotypes between south-Italian and Balkan populations (Gömöry et al 1999;Vettori et al 2004), reflected also in the direct relationship between Calabria and Balkan populations (Gre, Rod) shown in the reticulogram (Fig. 3) and the position of both groups in the neighbor-net network (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Peculiar is a genetic proximity and even partial sharing of chloroplast haplotypes between south-Italian and Balkan populations (Gömöry et al 1999;Vettori et al 2004), reflected also in the direct relationship between Calabria and Balkan populations (Gre, Rod) shown in the reticulogram (Fig. 3) and the position of both groups in the neighbor-net network (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test these hypotheses, we analysed chloroplast DNA (cpDNA) using the PCRrestriction fragment length polymorphism (RFLP) method. Organelle markers are uniparentally inherited and exhibit reduced effective population sizes; hence, they reveal a clearer picture of the genealogical history of a species than do nuclear markers (Vettori et al 2004). Previous studies have successfully used cpDNA markers to deduce the locations of glacial refugia and postglacial colonisation routes in Alnus glutinosa (King and Ferris 1998), Fagus sylvatica (Demesure et al 1996;Magri et al 2006), Fraxinus excelsior (Heuertz et al 2004), Quercus (Csaikl et al 2002;Petit et al 2002a, b), Populus (Cottrell et al 2005;Fussi et al 2010) and Betula (Palmé et al 2003;Maliouchenko et al 2007;Thórsson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The current geographical distribution of the haplotypes of a species is a result of contraction/expansion of the geographical range after climate fluctuations during the Quaternary period (Trewick et al 2000;Palme et al 2003) and/ or of topographical barriers to colonization, for example the main mountain ranges and oceans (Ferris et al 1998;Taberlet et al 1998;Lugon-Moulin et al 1999;Vettori et al 2004;Huang et al 2005). The spread and geographical boundary of the two haplotypes of clades I and II of F. crenata do not seem to be related to any topographical characteristics, e.g.…”
mentioning
confidence: 93%
“…This is because cpDNA is maternally inherited in most angiosperms (Hillis and Moritz 1990;Ennos 1994;Newton et al 1999). Several studies have revealed the geographical structuring of cpDNA variation at the population level, and the history of colonization or the location of refugia has been inferred in a variety of plant species (Ferris et al 1998;Taberlet et al 1998;Ohi et al 2003;Palme et al 2003;Vettori et al 2004;Huang et al 2005).…”
mentioning
confidence: 97%